SOCIAL NETWORKS AS A MEAN OF POLITICAL CONFRONTATION AND INFORMATION IMPACT - Kesoyan , H.A. (Modern Psychology, 2020)
In modern society the process of communication and transmutation of information through social media (social networks) has reached unprecedented levels. In this article, we have analyzed such obvious and hidden unique techniques and tools that are used to influence different target audiences in social media.
Keywords: Information Impact; Public Opinion; Users; Social Media; Mass Media; Cognitive Impairment.